2016
DOI: 10.1080/07391102.2015.1124807
|View full text |Cite
|
Sign up to set email alerts
|

Docking and molecular dynamics studies of peripheral site ligand–oximes as reactivators of sarin-inhibited human acetylcholinesterase

Abstract: In the present work, we performed docking and molecular dynamics simulations studies on two groups of long-tailored oximes designed as peripheral site binders of acetylcholinesterase (AChE) and potential penetrators on the blood brain barrier. Our studies permitted to determine how the tails anchor in the peripheral site of sarin-inhibited human AChE, and which aminoacids are important to their stabilization. Also the energy values obtained in the docking studies corroborated quite well with the experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Sequence alignment showed that PpAChE5 possessed most of the crucial structure features of AChEs family, including the important choline binding sites, catalytic triads functioning as a charge-relay system, a number of aromatic residues lining the catalytic gorge and six cysteine residues forming three intramolecular disulphide bridges. These conserved amino acids have been reported to play important roles in AChE functions [ 14 ]. However, this putative AChE also has some unique features, such as the ‘AGESAG’ instead of ‘FGESAG’ and only seven out of fourteen aromatic residues are conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence alignment showed that PpAChE5 possessed most of the crucial structure features of AChEs family, including the important choline binding sites, catalytic triads functioning as a charge-relay system, a number of aromatic residues lining the catalytic gorge and six cysteine residues forming three intramolecular disulphide bridges. These conserved amino acids have been reported to play important roles in AChE functions [ 14 ]. However, this putative AChE also has some unique features, such as the ‘AGESAG’ instead of ‘FGESAG’ and only seven out of fourteen aromatic residues are conserved.…”
Section: Discussionmentioning
confidence: 99%
“…5HF9 corresponds to the crystallographic structure of Hss AChE inhibited by POX and complexed with HI-6. This experimental structure was opened in the Discovery Studios ® Visualizer (DS ® Vis) 4.5 program [20], and had the missing loops PGGTGG and PKA and the C-terminal sequence EGR built through alignment to its FASTA sequence (code P22303) obtained from the Uniprot server (), following the same procedure adopted before [21], in order to obtain a complete model for the complex Hss AChE/POX. 4B0O corresponds to the crystallographic structure of Hss BChE inhibited by soman and complexed with benzyl pyridinium-4-methyltrichloroacetimidate (BP4M).…”
Section: Methodsmentioning
confidence: 99%
“…The complexes Ee AChE-POX/oxime were simulated using GROMACS 5.1.4 [ 68 ] package in a cubic box (941.59 nm 3 ) containing approximated 28,522 spc216 water molecules with periodic boundary conditions. The minimization steps were steepest descent with position restrained (PR) of ligands and protein, with a convergence criterion of 100.00 Kcal/mol.Å, steepest descent without PR to flexibilize the system, conjugate gradients (CG), and L-BFGS (limited-memory Broyden–Fletcher–Goldfarb–Shanno [ 24 ]), until a minimum of energy of 1.00 Kcal/mol.Å. After that, two steps of equilibration were done.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, studies are focused on looking for oximes that could be efficient against a larger number of OPs, conjugated with an appropriate penetration in the BBB. In this sense, neutral oximes ( Figure 2 ) have been proposed and studied by several authors [ 11 , 18 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%